Structural Optimization and Thermal Management with PCM-Honeycomb Combination for Photovoltaic-Battery Integrated System - Xinxi Li; Jiangyun Zhang; Dequan Zhou; Guoqing Zhang; Hongwei Wu; Rensheng Liu (International Journal of Photoenergy)
Power lithium–ion batteries retired from the electric vehicles (EVs) are confronting many problems such as environment pollution and energy dissipation. Traditional photovoltaic (PV) battery systems are exhibiting many issues such as being bulky and expensive, high working temperature, and short service span. In order to address these problems, in this study, a novel PV–battery device integrating PV controllers and battery module into an independent device is proposed. Phase change material (PCM) as the energy storage material has been utilized in battery module, and the aluminum honeycomb is combined with PCM to improve the heat conductivity under natural convection conditions. Three types of PV battery systems including the general PV–battery integrated system (G–PBIS), honeycomb PV–battery integrated system (H–PBIS), and honeycomb–paraffin PV–battery integrated system (HP–PBIS) have been investigated in detail. The results reveal that the maximum temperature of the HP–PBIS coupling with the double–layer 10×165×75 mm3 PCM was reduced to 53.72°C, exhibiting an optimum cooling effect among various PV battery systems. Thus, it can be concluded that the aluminum honeycomb provides the structural reliability and good thermal conductivity, and the PCM surrounding battery module can control the temperature rising and balance the temperature uniformly. Besides, the optimum PV–battery integrated system performs a promising future in energy storage fields.